2000
DOI: 10.1080/10286020008041372
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic Effects of Gymnemic Acid IV, a Compound Derived fromGymnema sylvestreLeaves in Streptozotocin-Diabetic Mice

Abstract: We investigated the antihyperglycemic action of a crude saponin fraction and five triterpene glycosides (gymnemic acids I-IV and gymnemasaponin V) derived from the methanol extract of leaves of Gymnema sylvestre R. BR. (Asclepiadaceae) in streptozotocin (STZ)-diabetic mice. The saponin fraction (60mg/kg) reduced blood glucose levels 2 4h after the intraperitoneal administration. Gymnemic acid IV, not the other 4 glycosides at doses of 3.4-13.4mg/kg reduced the blood glucose levels by 13.5-60.0% 6h after the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(97 citation statements)
references
References 13 publications
3
92
2
Order By: Relevance
“…Hypoglycemic effect of various triterpenoids and steroids from natural resources had been investigated and documented by various researchers (Sugihara et al, 2000;Tan et al, 2008;Hai-Xue et al, 2011). The extract is widely used and prescribed by tribal of India as an alternative or complementary diabetes treatment .…”
Section: Discussionmentioning
confidence: 99%
“…Hypoglycemic effect of various triterpenoids and steroids from natural resources had been investigated and documented by various researchers (Sugihara et al, 2000;Tan et al, 2008;Hai-Xue et al, 2011). The extract is widely used and prescribed by tribal of India as an alternative or complementary diabetes treatment .…”
Section: Discussionmentioning
confidence: 99%
“…fruits exhibited hypoglycemic, anti-peroxidative and anti-hyperlipidemic effects in Type I diabetic rats [128]. Charantin (XV) isolated from Momordica charantia L. possesses an insulin-like activity with which it promotes insulin secretion, and thereby lowers hepatic glycogenesis [129]. Also, diverse saponins such as β-sitosterol (XVI) present in Azadirachta indica A., andrographolide (XVII), a diterpenoid lactone, obtained from Andrographis paniculata Nees and gymnemic acid IV (XVIII) isolated from Gymnema sylvestre R., are agents of glycemic control in animal models [130,131].…”
Section: Saponinsmentioning
confidence: 99%
“…Many authors had isolated and identified GA earlier in leaf explants of methanol extracts. In 1989, Yoshikawa and co-workers isolated GAs from a hot water extract of G. sylvestre, which they named GA, I, II, III, IV, V, VI, and VII, respectively, and evaluated using HPLC [28,29]. The above mentioned OPGRs sample kept under abiotic stress conditions and the developed callus methanol extracts were further analyzed (Fig.…”
Section: Hplc Studies In Leaf and Callus Extractsmentioning
confidence: 99%